2014
DOI: 10.1590/0100-2945-144/13
|View full text |Cite
|
Sign up to set email alerts
|

Production and quality of Anacardium othonianum Rizz. seedlings grown in different substrates

Abstract: -This study aimed to evaluate the effect of substrate on growth, emergence, nutrition, and quality of Anacardium othonianum Rizz. (cerrado cashew tree) seedlings. The experiment was conducted in a greenhouse at the Plant Tissue Culture Laboratory on the Rio Verde campus. The following substrates were used: 1) Bioplant ® , 2) Mecplant ® (MP) + carbonized rice husk (CRH) (7:3), 3) fine-grained vermiculite (FGV), 4) FGV+CRH (3:1), 5) FGV+CRH (1:1), 6) FGV+CRH (1:3), and 7) sugarcane bagasse (SB) + sugarcane mill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
2
6
0
3
Order By: Relevance
“…The only substrate that had an AW within the optimal range of 0.24 to 0.40 m 3 m -3 according to Liz and Carrijo (2008) was FV+SB+DCS, whereas the other substrates had lower values, which may compromise their water availability. TP values are similar to those reported by Dornelles et al (2014) already AW of this study is intermediate to found by Dornelles et al (2014), except the FV + SB + DCS which was superior.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The only substrate that had an AW within the optimal range of 0.24 to 0.40 m 3 m -3 according to Liz and Carrijo (2008) was FV+SB+DCS, whereas the other substrates had lower values, which may compromise their water availability. TP values are similar to those reported by Dornelles et al (2014) already AW of this study is intermediate to found by Dornelles et al (2014), except the FV + SB + DCS which was superior.…”
Section: Resultssupporting
confidence: 88%
“…In addition, both PES and ESI were not correlated with available water. According to Nogueira et al (2003) and Dornelles et al (2014), to promote germination and emergence of a seedling, the substrate should exhibit a porosity that provides aeration and moisture for the seed, thereby providing water and oxygen for metabolism, given that a seedling does not require nutrients to germinate or emerge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the highest value (0.50) was obtained by SB+CM substrate, which however differed just of the SB+CC (0.31). Studying the development of Cerrado cashew tree seedlings in substrates with different proportions of fine-grained vermiculite + carbonized rice husk, sugarcane bagasse + sugarcane mill filter cake and substrates commercials, it was found an IQD between 0.34 and 0.48 (DORNELLES et al, 2014), values similar to verified this study. The DQI is considered a promising integrated measure of morphological traits and thought to be a good indicator of seedling quality as its calculation computes robustness and biomass distribution while considering several important parameters (FONSECA et al, 2002).…”
Section: Resultssupporting
confidence: 87%
“…To obtain these characteristics is often necessary mix two or more components, which together will form a suitable substrate for seedlings formation (Araújo Neto et al, 2009). Dornelles et al (2014) studied the development of Anacardium othonianum Rizz seedlings (Cerrado cashew tree) in substrates formulated with Mecplant® (MP) + carbonized rice husk (CRH) in 7:1 (v:v proportion), fine-grained vermiculite (FGV), FGV+CRH (3:1), FGV+CRH (1:1), FGV+CRH (1:3), and sugarcane bagasse (SB) + sugarcane mill filter cake (FC) (3:2). They verified that the substrate SB+FC (3: 2) promoted the best nutrition for plants.…”
Section: Parameters Of Physiology Nutrition and Quality Of Eugenia Dmentioning
confidence: 99%